El ejercicio del poder de dirección del empleador y sus límites frente a los derechos de los trabajadores - Jiménez Silva, Carlos (2022)
The information and communication technologies applied in labor relations have a series of constitutional implications on the limits of the use of the power of management, of which there have been different pronouncements, hence the academic interest. In order to develop this topic, we have resorted to the doctrine and, from a practical point of view to the Constitutional Court Rulings and Supreme Court Cassations. The article then deals with a brief introduction, followed by some general concepts on the power of direction, which is broken down into three powers: Regulatory Power, Supervisory Power and Sanctioning Power, including in each section the analysis and notes to the various case law cases.